Local Knowledge as the Basis of Innovation in Managing Agricultural Products - Jurry Foo; Muhammad Yasar; Mansoor Abdul Hamid; Diana Demiyah Binti Mohd Hamdan; Harifah Mohd Noor; Jalihah Md. Shah; Kee Sabariah Kee Yusof; Intan Soliha Ibrahim; Marja Azlima Omar; Pauline Yong; Colonius Atang; Hanif Abdurahman Siswanto (BASKARA : Journal of Business and Entrepreneurship, 2023)
The management of agricultural resources is an important agenda especially during the period of COVID-19 pandemic, which has increased food waste from agricultural products and the loss of sources of income among communities involved in agricultural activities. However, food waste remains as an urgent matter even in post-COVID-19 pandemic. This article aims to discuss about how local knowledge is used to deal with the agriculture waste. Vegetables dumping issues causing waste and affecting the income of farmers and vegetable sellers. Therefore, innovations in processing vegetables into processed food was implemented to optimize agribussines values. In achieving this goal, the steps to be taken are to empower the existing knowledge so called ‘local knowledge’. The information in producing this article was gathered through observation of community who participate voluntarily and interviews with Department of Agriculture, Federal Agricultural Marketing Authority (FAMA) and The Ministry of Agriculture and Food Industries and abbreviated (MAFI). The results of the study found that the main methods of food processing method by the community are preserving, drying, smoking or curing and frying. Hence this these methods were used to process cabbage (Brassica oleracea) into several products namely (1) cabbage floss, (2) salted cabbage, (4) cabbage bosou and (4) cabbage kimchi.